Theacrine From Camellia kucha and Its Health Beneficial Effects - Sheng, Yue-Yue; Xiang, Jing; Wang, Ze-Shi; Jin, Jing; Wang, Ying-Qi; Li, Qing-Sheng; Li, Da; Fang, Zhou-Tao; Lu, Jian-Liang; Ye, Jian-Hui; Liang, Yue-Rong; Zheng, Xin-Qiang (Frontiers in Nutrition, 2020)
Theacrine, i.e., 1,3,7,9-tetramethyluric acid, is one of the major purine alkaloids in leaves of a wild tea plant species Camellia kucha. Theacrine has been attracted great attentions academically owing to its diverse health benefits. Present review examines the advances in the research on the health beneficial effects of theacrine, including antioxidant effect, anti-inflammatory effect, locomotor activation and reducing fatigue effects, improving cognitive effect, hypnotic effect, ameliorating lipid metabolism and inhibiting breast cancer cell metastasis effect. The inconsistent results of this study and further expectations were also discussed.